The Role of Tissue Oxygen Tension in Dengue Virus Replication - Efseveia Frakolaki; Panagiota Kaimou; Maria Moraiti; Katerina I. Kalliampakou; Kalliopi Karampetsou; Eleni Dotsika; Panagiotis Liakos; Dido Vassilacopoulou; Penelope Mavromara; Ralf Bartenschlager; Niki Vassilaki (Cells, 2018)
Low oxygen tension exerts a profound effect on the replication of several DNA and RNA viruses. In vitro propagation of Dengue virus (DENV) has been conventionally studied under atmospheric oxygen levels despite that in vivo, the tissue microenvironment is hypoxic. Here, we compared the efficiency of DENV replication in liver cells, monocytes, and epithelial cells under hypoxic and normoxic conditions, investigated the ability of DENV to induce a hypoxia response and metabolic reprogramming and determined the underlying molecular mechanism. In DENV-infected cells, hypoxia had no effect on virus entry and RNA translation, but enhanced RNA replication. Overexpression and silencing approaches as well as chemical inhibition and energy substrate exchanging experiments showed that hypoxia-mediated enhancement of DENV replication depends on the activation of the key metabolic regulators hypoxia-inducible factors 1α/2α (HIF-1α/2α) and the serine/threonine kinase AKT. Enhanced RNA replication correlates directly with an increase in anaerobic glycolysis producing elevated ATP levels. Additionally, DENV activates HIF and anaerobic glycolysis markers. Finally, reactive oxygen species were shown to contribute, at least in part through HIF, both to the hypoxia-mediated increase of DENV replication and to virus-induced hypoxic reprogramming. These suggest that DENV manipulates hypoxia response and oxygen-dependent metabolic reprogramming for efficient viral replication.